2004
DOI: 10.1021/ma0401222
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Poly(ethylene imine) and Its Model Compounds:  Rotational and Inversional Isomerizations and Intramolecular and Intermolecular Hydrogen Bonds

Abstract: Conformational characteristics of poly(ethylene imine) (PEI) have been investigated by a rotational isomeric state (RIS) analysis of ab initio molecular orbital (MO) calculations and 1H and 13C NMR experiments for a monomeric model compound, N,N ‘-dimethylethylenediamine (di-MEDA). From the MO and NMR data, it was shown that the C−C and C−N bonds of di-MEDA have high gauche (71−93%) and trans (64−86%) preferences, respectively. Conformational energies of PEI were determined from the MO calculations for di-MEDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
75
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(78 citation statements)
references
References 47 publications
3
75
0
Order By: Relevance
“…Meanwhile, studies using quantum chemical calculations, which differ from RIS, MM and MD in that the experimentally obtained force field constants are not used, have been reported. [14][15][16][17][18][19][20] It is considered that this method is in a position to obtain accurate information of a single chain eliminating intermolecular interactions. Regarding PEO, Tsuzuki et al, 14 Smith et al 15,16 and Sasanuma et al 17 reported results using a monomer (dimethoxyethane) as a model of PEO.…”
mentioning
confidence: 99%
“…Meanwhile, studies using quantum chemical calculations, which differ from RIS, MM and MD in that the experimentally obtained force field constants are not used, have been reported. [14][15][16][17][18][19][20] It is considered that this method is in a position to obtain accurate information of a single chain eliminating intermolecular interactions. Regarding PEO, Tsuzuki et al, 14 Smith et al 15,16 and Sasanuma et al 17 reported results using a monomer (dimethoxyethane) as a model of PEO.…”
mentioning
confidence: 99%
“…Sasanuma et al 7 has reported that the characteristic ratios (P meso /P racemo ) of PEI chaines, which were evaluated from energy parameters, changed from 0.63/0.37 in gaseous state to 0.52/0.48 in the state that intra-molecular interaction (NHÁÁÁH) was neglected. The results estimated in present study support these evaluated results.…”
Section: Hydrate Effects On Trans/gauche Preferencesmentioning
confidence: 99%
“…Unlike the PEO solutions, the trans-fractions of the C-C bonds of the PEI solutions increase with increase of permittivity (") of solvents, based on NMR analyses of N,N 0 -dimethylethylenediamine (di-MEDA) as a model of PEI. 7 The conformation of PEI, in this manner, specifically depends on environmental factors. Unfortunately, detailed understandings of these environmental effects have yet to be clarified because of the complexity in these effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses for anhydrate models using molecular mechanics (MM) and molecular dynamics (MD) have been reported [5,6]. Furthermore, recent studies involve quantum chemical calculations method (QCC) [7][8][9]. The reports concerning an analysis using hydrate model of PEI, however, seem to be little [10].…”
Section: Introductionmentioning
confidence: 99%